PENGARUH BAHAN SHIELDING ALUMINIUM PADA PENYEBARAN GELOMBANG ELEKTROMAGNETIK PENGAPIAN SEPEDA MOTOR - , ALIFFAZRIE WAHYUTAMA YOSTO, Prof. Dr. Ir. T. Haryono, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The current technology improvement especially on the equipment that using modern system with taking advantage on wave lenght or frecuency can rise electromagnetic. Electromagnetic is a wave that spread even without medium. So that electromagnetic wave doesnât give any loss to the equipment function and doesnât affect the operational of the equipment, the equipment need a shielding to prevent emission and radiation from inside to out or from outside to inside so doesnât inflict interfrence from the result of magnetic field and electric field. On this research will discussed about magnetic field and electric field from motorcycle by sparking process inside the spark plugs that make EMI (Electromagnetic Interfrence) by observing amaount of the damping that can be muffled by alumunium and to know amaount of shielding effectiveness. Alumunium that used in this research has various thickness, they are 1 mm, 0.6 mm, 0.3 mm The result of this result shown that aluminium can be used as shielding material to reduce the impact of electromagnetic interference (EMI). The shielding effectiveness of magnetic field in 1mm thickness is 33 dB â 89 dB, and the electric field effectiveness is 334 dB â 358 dB.